Change in perspective, change in educational policy - Telor Reize, Dorit; Gluck, Sandy; Ostrizki, Luba (Frontiers in Education, 2025)
This policy brief explores how a shift in perspective changed the educational environment for EFL educators to improve student teachers’ oral performance. Grounded in action research, we present reflective, practice-based policies. A key finding of action research was the central role of social–emotional factors, specifically foreign language anxiety. The department began a process of expansive learning to integrate the ACCESSES framework (Autonomy, Collaboration, Communication, Empowerment, Scaffolding and Emotional Safety). This shift fostered a collaborative culture, addressed emotional needs in language learning, and led to instructional redesign. Core practices refined through ongoing professional development, transformed the departmental culture into a space of experimentation and applied theory. We redefined our teaching and learning, which became a model for broader institutional change.